POPULASI DAN INTENSITAS SERANGAN HAMA WALANG SANGIT (Leptocorisaoratorius) PADA BEBERAPA VARIETAS TANAMAN PADI SAWAH DI DESA TOLOTOYON KABUPATEN BOLAANG MONGONDOW SELATAN - Ayu Ningsih Paputungan; Jantje Pelealu; Daisy S. Kandowangko; Selvie Tumbelaka (COCOS, 2020)
ABSTRAKThe research aims to find out: (1). The population of walang sangit pest in several rice varieties inTolotoyon village, Bolaang Mongondow Selatan Regency; (2). pest attack wit sangit on severalvarieties of rice in the village Tolotoyon Bolaang Mongondow Regency.The study was carried outin a rice-growing area owned by farmers in Tolotoyon Village, Bolaang Mongondow SelatanRegency. The duration of the study is 3 (three) months, from December 2019 to February 2020.Bandage using Random Group Design (RAK) with the treatment of rice plant varieties, namelyCiherang, Inpari 9, and Situ bagendiT and repeated three times. The research was conducted atthree locations, each measuring approximately one (1) hectare. Each location planted one variety.Sampling was conducted three (3) times. Sampling is carried out on plants that are ten weeks oldwith a retrieval interval of one (1) week. Parameter the number of nymphs and image caught.Observation of the intensity of pest attacks is carried out visually based on the symptoms ofWalang Sangit attack on the malaise of rice crops. Observations are made on generative phase riceplants. Parameter the number of malaises affected. The results showed that the highest walangsangit pest population was found in the Ciherang variety of 6.8 Walang Sangits, followed by Inpari9 which is 5.6 Walang Sangits and the lowest in Situ bagendit which is 3.1 The yield on walangsangit pest attacks on inpari varieties was 7.0 percent, followed by Ciherang 6.1 percent, whileSitu Bagendit 3.1 percent.The difference in population and intensity of Walang Sangit pest attackson some varieties of rice crops, caused by the character of rice crops, such as the number of shootsand the color of grain.Keywords : Rice varieties,Leptocorisa Oratorius, population, and intensity